2005
DOI: 10.1021/ja0506859
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Binding Sites in Thiol-Functionalized Mesostructured Silica

Abstract: Thiol-functionalized mesostructured silica with anhydrous compositions of (SiO(2))(1)(-)(x)()(LSiO(1.5))(x)(), where L is a mercaptopropyl group and x is the fraction of functionalized framework silicon centers, are effective trapping agents for the removal of mercuric(II) ions from water. In the present work, we investigate the mercury-binding mechanism for representative thiol-functionalized mesostructures by atomic pair distribution function (PDF) analysis of synchrotron X-ray powder diffraction data and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
107
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 38 publications
2
107
0
Order By: Relevance
“…8). This represents an advantage of PAF-1-SH for mercury removal across a wide range of pH, particularly when compared with silica and MOFs based adsorbents [12][13][14][15][16][29][30][31][32][33][34] , which usually suffer from the loss of porosity under such harsh conditions. Mercury adsorption experiments under acid and basic conditions revealed that PAF-1-SH also exhibits high affinities for Hg(II) with K d values of 6.66 Â 10 7 ml g À 1 at pH 1.0 and 2.49 Â 10 7 ml g À 1 at pH 12.8, which render excellent capability of reducing Hg(II) concentrations from 10 p.p.m.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…8). This represents an advantage of PAF-1-SH for mercury removal across a wide range of pH, particularly when compared with silica and MOFs based adsorbents [12][13][14][15][16][29][30][31][32][33][34] , which usually suffer from the loss of porosity under such harsh conditions. Mercury adsorption experiments under acid and basic conditions revealed that PAF-1-SH also exhibits high affinities for Hg(II) with K d values of 6.66 Â 10 7 ml g À 1 at pH 1.0 and 2.49 Â 10 7 ml g À 1 at pH 12.8, which render excellent capability of reducing Hg(II) concentrations from 10 p.p.m.…”
Section: Synthesismentioning
confidence: 99%
“…Conventional adsorbents such as activated carbons 7 , zeolites 8 and clays 9 generally have low capacity and weak binding affinity for mercury. Thiol/thio-functionalized adsorbents, including clays 10 , resins 11 , mesoporous silica [12][13][14][15][16] , activated carbons 17 , mesorporous carbons 18 and chalcogenides 19,20 , are considered very effective sorbents for Hg(II) removal from aqueous solutions due to the soft-soft interaction 21 . Recently, metal-organic frameworks (MOFs) [22][23][24][25][26][27][28] have been explored as a new type of adsorbents for mercury removal [29][30][31][32][33][34] due to their high surface areas, but they usually suffer from instability in water 29,30 or aqueous solutions with a wide pH range 34 and possess low adsorption capacity and weak affinity for Hg(II).…”
mentioning
confidence: 99%
“…The Stöber method has often been used for synthesis of organosilica particles through condensation of tetraethoxysilane (TEOS) 6,7 or TEOS co-condensation with other functional silanes, such as 3-aminopropyltriethoxysilane (APTS) [8][9][10] and 3-mercaptopropyltrimethoxysilane (MPTS). [10][11][12] The typical size of organosilica particles synthesized using Stöber conditions is often greater than 500 nm. 6,7,9 The Stöber method was also used to generate mesoporous materials, where homo-or co-condensation of TEOS with other functional silanes was conducted in the presence of low molecular weight or polymeric surfactants as a template.…”
Section: Introductionmentioning
confidence: 99%
“…These attractive pore systems have been used for numerous applications including molecular and clusterbased catalysis, [2] selective sequestration of contaminants [3] and chromatography, [4] stabilization of conducting nanoscale wires, [5] and as novel drug-delivery systems. [6] For many of these applications, the mesoporous materials are expected to show enhanced properties when their inner channel walls are functionalized with organic moieties to fine-tune hostguest interactions.…”
Section: Introductionmentioning
confidence: 99%